(untitled) - Dyer, Jeffrey (Boston, Massachusetts, 2019)
We've all seen leaders who excel at winning resources and support for their ideas. It turns out that this quality is so valuable, and measurably more important for innovation than just being creative, that it has a name: "innovation capital." Contrary to popular belief, effective leaders of innovation--folks like Thomas Edison, Steve Jobs, Jeff Bezos, and Elon Musk--are successful not only because of the quality of their ideas but because they have the reputation and networks to successfully commercialize creative ideas. Nikola Tesla was arguably a more brilliant inventor than Thomas Edison, but Edison was able to realize tremendous commercial success while Tesla died penniless. Innovation Capital reveals the critical ingredient that separates the people who can marshal the resources necessary to turn their ideas into reality from those who can't, and shows you how to acquire, amplify, and use it to succeed as an innovative leader. Authors Jeff Dyer, Nathan Furr, and Curtis Lefrandt have spent decades studying how people get great ideas (the subject of The Innovator's DNA) and how people test and develop those ideas (explored in The Innovator's Method). Now, they share what they have learned from a multipronged research program designed to understand how people compete for, and obtain, resources to launch innovative new ideas--even, in some cases, before they've earned a track record of innovation.
Keywords: Thành công trong kinh doanh,Success in business